Еstimation of the beam power gain for deep-subcritical uranium assembly Quinta under relativistic proton, deuteron and carbon nuclei irradiation - Voronko, V.А.; Zhadan, А.А.; Sotnikov, V.V.; Adam, I.; Baldin, А.А.; Berlev, A.I.; Solnyshkin, A.А.; Tyutyunnikov, S.I.; Furman, W.I.; Husak, K.V; Zhuk, I.V (Вопросы атомной науки и техники, 2018)
The experimental study of the beam power gain for deep-subcritical uranium target assembly Quinta (mass of
natural uranium 512 kg) under relativistic protons, deuterons and carbon nuclei irradiation is presented. The Quinta
assembly was irradiated with 0.66 GeV protons, 1, 2, 4, and 8 GeV deuterons and 24, 48 GeV carbon nuclei from
the Phasotron and Nuclotron accelerators at the Joint Institute for Nuclear Research (JINR), Dubna. The beam power gain values obtained for the target assembly Quinta were extrapolated for a quasi-infinite uranium target using the
results of the R.G. Vasilkov et al. [1]. The obtained results can be used in the ADS reactor design. Представлені результати експериментального визначення коефіцієнтів посилення потужності первинного
пучка при опроміненні релятивістськими протонами, дейтронами і ядрами вуглецю глибоко підкритичної уранової збірки КВІНТА (512 кг natU). Збірка КВІНТА опромінювалася 0,66 ГеВ протонами; 1, 2, 4 і 8 ГеВ дейтронами і 24, 48 ГеВ ядрами вуглецю на прискорювачах ФАЗОТРОН і НУКЛОТРОН Об’єднаного інституту ядерних досліджень (ОІЯД), м. Дубна. Значення коефіцієнтів посилення потужності для збірки КВІНТА були екстрапольовані для квазібезкінечної уранової мішені c використанням результатів роботи [1]. Отримані результати можуть бути використані при проектуванні ADS установок. Представлены результаты экспериментального определения коэффициентов усиления мощности первичного пучка при облучении релятивистскими протонами, дейтронами и ядрами углерода глубоко подкритичной
урановой сборки КВИНТА (512 кг natU). Сборка КВИНТА облучалась 0,66 ГэВ протонами; 1, 2, 4 и 8 ГэВ дейтронами и 24, 48 ГэВ ядрами углерода на ускорителях ФАЗОТРОН и НУКЛОТРОН Объединенного института
ядерных исследований (ОИЯИ), г. Дубна. Значения коэффициентов усиления мощности для сборки КВИНТА
были экстраполированы для квазибесконечной урановой мишени c использованием результатов работы [1].
Полученные результаты могут быть использованы при проектировании ADS установок.